(untitled) (Journal of Educational Sciences, 2017)
The data on emotional intelligence obtained during empirical research demonstrate, that students have the sufficient level of knowledge for development of emotional intelligence, emotional motivation. At the same time, even in the presence of knowledge of the emotional sphere, of emotions and feelings, practical manifestation of emotional intelligence is given more difficult. Therefore it is very important, on the basis of the available knowledge and internal motivation, to teach future expert to develop elements of emotional intelligence as bases of formation of culture of intellectual work in a complex. The emotional intelligence as the measured ability to understand emotions, to consciously regulate emotions, to distinguish and express emotions helps to use emotions as cogitative activity as bases for drawing up a psikhogramma of future expert, her contents as a compound component of technology of formation of culture of intellectual work.